Activity of the cyclooxygenase 2-prostaglandin-E prostanoid receptor pathway in mice exposed to house dust mite aeroallergens, and impact of exogenous prostaglandin E2 - Marco Alberto; Serra Mariona; Torres Rosa; Herrerias Aida; Pujols Laura; Picado César; de Mora Fernando (BMC, 2009)
Abstract Background Prostaglandin E2 (PGE2), experimentally administered to asthma patients or assayed in murine models, improves allergen-driven airway inflammation. The mechanisms are unknown, but fluctuations of the endogenous cyclooxygenase (COX)-2/prostaglandin/E prostanoid (EP) receptor pathway activity likely contribute to the clinical outcome. We analyzed the activity of the pathway in mice sensitized to aeroallergens, and then studied its modulation under exogenous PGE2. Methods Mice were exposed to house dust mite (HDM) aeroallergens, a model that enable us to mimic the development of allergic asthma in humans, and were then treated with either subcutaneous PGE2 or the selective EP1/3 receptor agonist sulprostone. Simultaneously with airway responsiveness and inflammation, lung COX-2 and EP receptor mRNA expression were assessed. Levels of PGE2, PGI2, PGD2 were also determined in bronchoalveolar lavage fluid. Results HDM-induced airway hyperreactivity and inflammation were accompanied by increased COX-2 mRNA production. In parallel, airway PGE2 and PGI2, but not PGD2, were upregulated, and the EP2 receptor showed overexpression. Subcutaneous PGE2 attenuated aeroallergen-driven airway eosinophilic inflammation and reduced endogenous PGE2 and PGI2 production. Sulprostone had neither an effect on airway responsiveness or inflammation nor diminished allergen-induced COX-2 and PGE2 overexpression. Finally, lung EP2 receptor levels remained high in mice treated with PGE2, but not in those treated with sulprostone. Conclusion The lung COX-2/PGE2/EP2 receptor pathway is upregulated in HDM-exposed mice, possibly as an effort to attenuate allergen-induced airway inflammation. Exogenous PGE2 downregulates its endogenous counterpart but maintains EP2 overexpression, a phenomenon that might be required for administered PGE2 to exert its protective effect.